Evaluasi atas Ketaatan Laporan Keuangan Koperasi dalam Kaitannya dengan PSAK No.27 pada Koperasi KOPTI Kabupaten Bogor - Djanegara, H. Moermahadi Soerja; Kurniawan, Kurniawan (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2006)
KOPTI Co-operative of Bogor Regency has done accounting practice in recording all finance transaction. That matter could be looked at Financial Report of KOPTI co-operative on yearly members meeting. Nowadays Financial Report of KOPTI comprises balance and dividend calculation accounting. This research has purpose to find out the application of Finance Accounting Standard Statement (PSAK) No. 27 as a compass for accounting practice and finance accounting arrangement by co-operative venture. Keywords: Financial Report; PSAK No. 27.